The Contribution of Eye-Hand Coordination to Shooting Accuracy in Basketball - Muhammad Rusli; Muhtar Asshagab; Jud (Athena: Physical Education and Sports Journal, 2026)
This study aims to analyze the contribution of hand-eye coordination to shooting accuracy in basketball. The study used a quantitative approach with a correlational design. The study population consisted of 395 students, consisting of 211 female students and 184 male students. The sample was determined using a purposive sampling technique based on the criteria of male students who had experience in basketball lessons, resulting in 35 students as research samples. The instrument used to measure hand-eye coordination was a tennis ball throw-catch test, while shooting accuracy was measured using a basketball shooting test conducted from several points around the ring. Data were analyzed using Pearson product moment correlation at a significance level of 5%. The results of the analysis showed that there was a positive and significant relationship between hand-eye coordination and shooting accuracy in basketball, with a correlation coefficient value of r = 0.58, greater than r table = 0.334. The coefficient of determination value of 34% indicates that hand-eye coordination contributed 34% to shooting accuracy, while the remaining 66% was influenced by other factors, such as muscle strength, balance, shooting technique, concentration, and training experience. It was concluded that eye-hand coordination is a crucial factor contributing to improved shooting accuracy in basketball, and therefore, its development should be part of basketball training and instructional programs in schools.